Imaging of the Adolescent Breast - Jones, Katie N. (Seminars in Plastic Surgery, 2013)
The mainstay of breast imaging in the adolescent is ultrasonography. There is occasionally a need for additional imaging, particularly with magnetic resonance imaging (MRI). Imaging of the adolescent breast differs substantially from the adult in both the imaging modalities utilized and the relative likelihood of pathologies encountered. The majority of lesions in the adolescent are benign, but the presence of a breast lesion may cause anxiety to patients and their families due to the wide awareness of breast malignancy in the adult population. It is important to be aware of the imaging modalities available to image the adolescent breast to prevent unnecessary radiation exposure while answering the clinical question. The current recommendations for adolescent diagnostic and screening breast imaging will be reviewed. Benign breast lesions such as fibroadenomas, fibrocystic change, pseudoangiomatous stromal hyperplasia, gynecomastia, and posttraumatic or infectious lesions with their associated imaging findings and management will be outlined. Additionally, review of breast malignancies that can affect adolescents will provide the reader with features to distinguish benign from malignant processes in the adolescent based on imaging findings and clinical presentation.
Keywords: breast; adolescent; imaging; mammogram; ultrasound; magnetic resonance imaging